Autoimmune hypoglycaemia caused by alpha-lipoic acid: a rare condition in Caucasian patients - A Veltroni (Endocrinology, Diabetes & Metabolism Case Reports, 2018)
Insulin autoimmune syndrome (IAS), a rare cause of autoimmune hyperinsulinaemic hypoglycaemia, is relatively well known in Japan. The incidence in Caucasians is less than one-fifth of that reported in Japanese people, but it is becoming increasingly recognised worldwide in non-Asians as well. Drugs containing sulphydryl groups are known to be associated with the disease in genetically predisposed individuals. Moreover, several recent reports showed a direct association between the onset of IAS and the consumption of dietary supplements containing alpha-lipoic acid (LA). Insulinoma remains the most prevalent cause of hypersulinaemic hypoglycaemia in Caucasians. Consequently, primary investigation in these patients is generally focused on localisation of the pancreatic tumour, often with invasive procedures followed by surgery. We described a case of an Italian woman presenting to us with severe recurrent hypoglycaemia associated with high insulin and C-peptide levels and no evidence of pancreatic lesions at imaging diagnostic procedures. She had taken LA until 2 weeks before hospitalisation. After an evaluation of her drug history, an autoimmune form of hypoglycaemia was suspected and the titre of insulin autoantibodies was found to be markedly elevated. This allowed us to diagnose LA-related IAS, thus preventing any unnecessary surgery and avoiding invasive diagnostic interventions.